Productivity of Wheat under a Populus deltoides Agroforestry System in the South-east of Central India - Puri, Sunil; Sharma, Amita (Indian Forester, 2002)
A study was conducted in the vertisol of Chhattisgarh, in South east of Central India, to see the effect of Populus deltoides on the productivity of wheat crop. Wheat was grown as intercrop under five different clones (G3, 65/27, D121, G48 and S7Cl). Data on crop growth and yield at different distances (0.5 m, 1.5 m and 2.0 m) and four directions (east, west, north and south) from the tree bases and control ( no trees) were collected. Results indicate that grain yield was found to be less near the tree and it increased with an increase in distance away from the tree. Wheat yield in the four directions of tree was maximum (12.3 q/ha) in the North of tree followed by West and South. Wheat productivity was affected by the P. deltoides clones. A grain yield of 14.0 q/ha was obtained in the sole crop. It was maximum (13.8 q/ha) under D121 clone and the order of grain yield reduction due to clone was: S7Cl > G48> G3 > 65/27 > D121.